Current applications of single shoulder-Specific or upper extremity region-specific patient-reported outcome measures in swimmers: a critically appraised topic - Sutherlin, M. A. (International Journal of Athletic Therapy & Training, 2020)
Clinical Question: What single shoulder-specific or upper extremity region-specific patient-reported outcome (PRO) measures (I) are used to assess self-perceived disability (O) in competitive swimmers (P)?